Artist Jean Luc Raharimanana talks with Dr. Cassandra Mark-Thiesen - Raharimanana, Jean Luc; Mark-Thiesen, Cassandra (Cluster Conversations, 2023)
In the month of May 2023, the poet and musician Jean Luc Raharimanana from Madagascar was invited by the Cluster of Excellence to accompany the Cluster's events and record his observations. In this episode of the Cluster Conversations Junior Research Group Leader Dr. Cassandra Mark-Thiesen took the opportunity to talk to the malagassy artist about paralells between her work and his.